2001
DOI: 10.1152/ajplung.2001.281.2.l499
|View full text |Cite
|
Sign up to set email alerts
|

Gene suppression by tristetraprolin and release by the p38 pathway

Abstract: Tristetraprolin (TTP) is a zinc finger protein that has been implicated in the control of tumor necrosis factor (TNF) mRNA stability. We show here that TTP protein has a suppressive effect on promoter elements from TNF-alpha and interleukin-8 and that lipopolysaccharide (LPS) stimulation can release this suppression. The release in LPS-stimulated cells was found to be primarily mediated by the p38 pathway because activation of p38 is sufficient to remove the suppressive effect of TTP. Indeed, TTP seems to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 36 publications
5
73
0
Order By: Relevance
“…Other studies exploring this question have reported varying results (22)(23)(24)(25). Carballo et al reported that phosphorylated TTP bound less to a granulocyte macrophage-colony stimulating factor ARE probe than dephosphorylated TTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies exploring this question have reported varying results (22)(23)(24)(25). Carballo et al reported that phosphorylated TTP bound less to a granulocyte macrophage-colony stimulating factor ARE probe than dephosphorylated TTP.…”
Section: Discussionmentioning
confidence: 99%
“…However, zinc fingers alone were not sufficient to mediate TNF-␣ mRNA degradation, because truncation of either the carboxyl or amino ends of TTP caused a loss TTP function (21). Both ends of the TTP zinc fingers contain a cluster of phosphorylation sites (22), yet the effects of phosphorylation on the mRNA binding and destabilizing activity of TTP remain controversial (22)(23)(24)(25).…”
Section: Tumor Necrosis Factor-␣ (Tnf-␣)mentioning
confidence: 99%
“…As previously described, TTP promotes TNFa mRNA instability in mouse macrophages through direct interactions with its ARE (Taylor et al, 1996a;Carballo et al, 1997Carballo et al, , 1998Carballo et al, , 2000. It has recently been shown that TTP activation requires phosphorylation by p38 (Zhu et al, 2001). Although TTP is directly activated by p38, it exists in several phosphorylation states in cells, and the involvement of other kinases cannot be excluded (Zhu et al, 2001).…”
Section: Regulation Of Are-binding Proteinsmentioning
confidence: 97%
“…It has recently been shown that TTP activation requires phosphorylation by p38 (Zhu et al, 2001). Although TTP is directly activated by p38, it exists in several phosphorylation states in cells, and the involvement of other kinases cannot be excluded (Zhu et al, 2001).…”
Section: Regulation Of Are-binding Proteinsmentioning
confidence: 99%
“…It is wellknown that TTP is a highly phosphorylated protein in mammalian cells (3,(20)(21)(22)(23)25). Phosphorylation of TTP in mammalian cells partially inhibits its binding to GM-CSF mRNA ARE and enhances its binding to the 14-3-3 protein (20,25).…”
mentioning
confidence: 99%